0270 Mortality from lung cancer in occupations with exposure to asbestos among men in england and wales (1979–2010). (21st August 2017) - Harris, E Clare; D'Angelo, Stefania; Palmer, Keith T; Cox, Vanessa; Darnton, Andrew; Coggon, David
Abstract : Background: Estimating national burdens of lung cancer from occupational exposure to asbestos is challenging because of the potential for confounding by smoking. Methods: To generate a refined estimate, we analysed data on underlying cause of death and last full-time occupation for 3, 688, 916 deaths among men aged 20–74 years in England and Wales during 1979–2010, calculating proportional mortality ratios (PMRs) standardised for age and social class. We compared observed and expected deaths from lung cancer in 28 occupations with excess mortality from mesothelioma or asbestosis. To reduce the confounding effects of smoking, we adjusted the expected number of lung cancers in each occupation, according to its PMR for chronic obstructive pulmonary disease (COPD) in an analysis that excluded jobs with a known hazard of COPD. Results: Adjusted PMRs for lung cancer were elevated in all but one of the 28 asbestos-exposed occupations, but did not correlate with those for cancer of the pleura (Spearman correlation coefficient=−0.3). The total excess of deaths from lung cancer across the 28 occupations over the 31 years of study was 9561 (as compared with 3164 when no adjustment was made). Conclusions: Asbestos appeared to account for some 300 excess lung cancer deaths per year in England and Wales, which is approximately 70% of the annual number of deaths from mesothelioma. The lack of correlation between PMRs for the two diseases may reflect different exposure-response relationships.